A Higher Preoperative Glycemic Profile Is Associated with Rapid Gastric Emptying After Sleeve Gastrectomy for Obese Subjects - Yang, Po-Jen; Cheng, Mei-Fang; Yang, Wei-Shiung; Tsai, Ming-Shian; Lee, Po-Chu; Chen, Chiung-Nien; Lin, Ming-Tsan; Tseng, Ping-Huei (Obesity surgery, 2019)
Background Recent reports have shown that sleeve gastrectomy (SG) accelerates gastric emptying (GE), but the etiology remains unclear. This study aimed to investigate the factors affecting GE before and after SG. Methods We enrolled 35 normal weight healthy subjects and 23 obese patients receiving SG. The normal individuals and obese patients before and 3 months after SG received oatmeal-based scintigraphy to measure GE. Gastrointestinal symptoms and circulating levels of peptide YY (PYY) were also measured. Results There were no differences in the GE parameters, including simple half-time at 3 h and percentage of gastric retention at 0.5, 1, 2, and 3 h between healthy controls and pre-SG obese subjects. SG led to accelerated GE, more gastrointestinal symptoms, and increased fasting PYY levels postoperatively. Based on our previously established normal GE values, 18 (78.3%) obese patients with rapid postoperative GE had higher levels of preoperative fasting glucose and glycated hemoglobin, and homeostasis model assessment of the insulin resistance index than those with normal postoperative GE. Twelve (52.2%) obese patients had preoperative diabetes mellitus (DM), and only four (17.4%) remained diabetic after SG. The post-SG gastric retention at 0.5 and 1 h was lower in patients with preoperative DM than in those without preoperative DM. Neither severity of gastrointestinal symptoms nor fasting PYY levels were associated with postoperative GE alterations. Conclusion Most of the obese patients had accelerated GE after SG. A higher preoperative glycemic profile was associated with rapid post-SG GE.